(untitled) (Dhaka Shishu (Children) Hospital Journal, 2026)
Background: Invasive fungal infections (IFIs) are a growing concern in critically ill and immunocompromised pediatric populations, particularly in low-resource settings. Factors such as prolonged hospitalization, use of broad-spectrum antibiotics, and hematologic malignancies contribute to increased risk. However, there is limited regional data from Bangladesh. Objective: To assess the prevalence, spectrum, and outcomes of IFIs among immunocompromised children in a tertiary care hospital in Bangladesh. Methods: This cross-sectional study was carried out at the Department of Paediatric Hemato-Oncology, Bangladesh Shishu Hospital & Institute, from October 2023 to March 2024. A total of 110 children under 18 years of age, with an absolute neutrophil count (ANC) below 500/μL and a fever persisting for more than 3-4 days, clinically suspected of having an invasive fungal infection, were enrolled in the study. Children over 18 years of age, those with normal eosinophil counts, or with no history of fever were excluded. Information on symptoms, test results, and outcomes was collected. Blood cultures and organ-specific samples were used to detect fungal infections. Results: Among the 110 children, 27 (24.5%) were diagnosed by PCR as fungal infections. The majority (44.4%) were £5 years old, and 63.0% were male. Acute lymphoblastic leukemia was the most common comorbidity (63.0%). PCR was positive in 51.9% of cases. The predominant pathogens were Candida albicans (25.9%) and Aspergillus fumigatus (22.2%), followed by Mucor and Aspergillus flavus (14.8% each). An overall survival rate of 92.6% was observed. Conclusion: Invasive fungal infections (IFIs) were identified in 24.5% of cases, with Candida and Aspergillus species being the most common pathogens. Early diagnosis and prompt initiation of targeted antifungal therapy were key factors in achieving favorable outcomes. The overall survival rate was high at 92.6%. DS (Child) H J 2024; 40(1): 46-50